Abandoned housing projects in Malaysia: Pressing issues during the rehabiliation process - Abdullah, Abdul Aziz; Abdul Rahman, Hamzah; Alashwal, Ali M. (2013)
Abandoned of housing projects during construction is a prevailing problem that the housing sector in Malaysia has been experiencing since 1980s. This paper aims to highlight the causes and impacts of abandoned housing projects, and various initiatives to rehabilitate these projects. Factors pertaining to projects abandonment can be categorized into: economic, financial, legal, managerial, system-related, and unforeseen risks. The study reveals three main impacts of abandoned housing projects: social, economic, and environmental impacts. The main steps taken to solve this problem include the rehabilitation of abandoned projects and other initiatives to reserve the right of purchasers through appropriate legal resolutions endorsement. Additional initiatives and formulation of upgraded solutions would further strengthen and enhance the ongoing policy of preempting and resuscitating abandoned housing projects. The study suggests further research to be conducted to identify various risks involved in the rehabilitation process. Such research can be aided through the seeking of stakeholders’ opinions on the risks to carry out projects rehabilitation.